Prescribing Placebos: An Experimental Examination of the Role of Dose, Expectancies, and Adherence in Open-Label Placebo Effects. Issue 1 (14th March 2018) - El Brihi, Jason; Horne, Rob; Faasse, Kate
Abstract : Open-label placebos enhanced psychological and physical wellbeing in healthy participants; positive baseline expectations and greater treatment adherence contributed to larger placebo effects. Abstract: Background: Recent evidence indicates that placebo effects can occur even when patients know that they are taking a placebo, termed the open-label placebo effect. Aim: To assess whether placebo dose (one pill per day vs. four pills per day), treatment expectancies, and adherence contribute to open-label placebo effects. Method: Healthy undergraduate participants were randomly assigned to take one or four open-label placebo pills per day or to a no-treatment control group. Placebo-treated participants took a 5-day course of an open-label placebo described as enhancing physical (symptoms and sleep) and psychological (positive and negative emotional experience) well-being. Expectancies about placebo effectiveness and well-being were assessed at baseline, and well-being and adherence were assessed after the 5-day course of treatment. Results: Medium-to-large open-label placebo effects were evidenced in all well-being outcomes including sleep quality. Dose did not influence these effects. Both treatment expectancies and adherence were significant independent predictors of enhanced well-being in the two psychological well-being outcomes and the experience of physical symptoms, but sleep quality improved independently. Conclusions: This is the first study to demonstrate the effect of open-label placebos in improving well-being and sleep quality and to show that open-label placebo reposes do not appear to be dose-dependent, but for most well-being outcomes are independently predicted by both positive expectancies and treatment adherence.